POTENSI BUDIDAYA IKAN GURAME DI WANASIGRA CIAMIS MELALUI PEMBUATAN KOLAM BUNDAR - Dedi Nurjamil; Asep Saepulloh; Endah Listyasari; Elis Nurhayati (LPPM Universitas Bina Bangsa, 2021)
Carp cultivation can be done in the form of a round pond that can be done in the yard. The purpose of this activity is to improve the quality and quantity of carp using a round pond. The implementation of community service is carried out for 3 months, starting from August to October 2021. Activities are carried out starting from planning, namely collaborating with UMKM and the Wanasigra village head, then carrying out the making of a circular pond to evaluation. The conclusion after carrying out the service was that the service activity by making a round fish pond was responded positively by the training participants. Good potential to be developed because it has a positive impact and can be an additional income, and can be applied in their respective homes